A Protocol for Preconceptional Screening of Consanguineous Couples Using Whole Exome Sequencing - Santos, Carolina Maria de Araújo dos; Heller, Ana Helena; Pena, Heloisa Barbosa; Pena, Sérgio Danilo Junho (Frontiers in Genetics, 2021)
Genetic studies performed in consanguineous couples suggest that the reproductive risk that distinguish them from other couples in the general population is related to autosomal recessive (AR) diseases. This risk is scattered among the thousands of known and potential AR diseases. Thus, for effective preconceptional screening of consanguineous couples it is necessary a test that encompasses the largest number of genes possible. For that reason, we decided to create a protocol based on whole exome sequencing (WES). We sequenced completely the exomes of 39 consanguineous couples at high coverage (∼100×). Applying bioinformatics filters, we could detect genetic variants that were simultaneously present in both members of the couple in all genes listed in the Clinical Genomics Database as causally related to AR diseases. Shared variants were then assessed for pathogenicity. For non-truncating variants (missense and in-frame indels) we considered as pathogenic or likely pathogenic only the variants included as such in the ClinVar database. Shared truncating variants (frameshift, non-sense, and canonical splice variants) were considered likely pathogenic when loss-of-function was a known mechanism of disease. The 39 consanguineous cases included two couples with a coefficient of genetic relationship (CGR) of 0.25, 26 couples with a CGR of 0.125, three couples with a CGR of 0.0625 and eight couples with a CGR of 0.03125. In 21 of the 39 couples (53.8%) we ascertained sharing of heterozygosity for at least one variant considered pathogenic or likely pathogenic for an AR disease. In eight couples we found sharing of heterozygosity for at least two pathogenic variants. Once the specific pathogenic variant was identified, it became possible for the couple to undergo prenatal diagnosis or, if desired, preimplantation genetic diagnosis (PGD) involving in vitro fertilization and embryo screening. In conclusion, our results demonstrate that preconceptional screening by WES is a useful new procedure that should be incorporated in the genetic counseling of all consanguineous couples.